Hubungan Antara Kelengkapan Informasi Medis Dengan Keakuratan Kode Diagnosis Tuberkulosis Pada Dokumen Rekam Medis Rawat Inap di Rumah Sakit Umum Daerah Dr. Moewardi - Nur Rahmawati, Eni, Sri Sugiarsi, SKM, M.Kes, Yuli Kusumawati, SKM., M. Kes (Epid) (2016)
The Completeness of medical information as the results of tuberculosis diagnosis is very important and it affects to the accuracy of the code. The accuracy of the tuberculosis diagnosis code is relied on a code-writing diagnosis that must be appropriate to the classification in the ICD-10. The code is considered precise and accurate when the code is appropriate to the patient's condition with all the procedures and the medical information must be complete based on classification rule used. The inaccurate code impacts on health care costs. The purpose of this study is to determine the relationship between the completeness of medical information with the accuracy diagnosis code of tuberculosis on inpatients medical records documents at Dr. Moewardi hospital in 2015. The type and design of this study uses observational analytic with cross sectional approach. The population of the study is 724 inpatients medical records documents. The sampling technique uses simple random sampling technique and it needs 73 medical records documents. The statistical test uses Fisher Exact by using SPSS. The results shows that there is no relationship between the completeness of medical information with the accuracy diagnosis code of tuberculosis on inpatients medical records documents at Dr. Moewardi hospital in 2015 (p= 0.159).